Levels of platelet derived extracellular vesicles in the left atrial appendage are higher in patients with permanent atrial fibrillation. (25th November 2020) - Zietzer, A; Al-Kassou, B; Jamme, P; Steffen, E; Werner, N; Nickenig, G; Jansen, F
Abstract: Introduction: Atrial fibrillation (AF) is a frequent arrhythmic disease and one of the most important causes of thrombembolic disease due to intracardiac thrombus formation. The left atrial appendage has been identified as the structure, where thrombus formation typically takes place in AF patients. Previous studies have shown thrombus formation is more frequent in permanent, than in paroxysmal or persistent AF. Underlying causes for this finding, however, remain unclear. Recently, it has been shown, that large extracellular vesicles (Microvesicles, MVs) are mediators of platelet activation. The aim of this study is therefore to investigate if the AF subtype correlates with the regional abundance of platelet derived MVs in the left atrial appendage. Methods and results: In order to address this question blood samples from 59 consecutive patients undergoing left and right atrial catheterization were collected from the right atrium (RA), the left atrium (LA) and the left atrial appendage (LAA). 49% of the patients had permanent AF, 34% had non-permanent AF and 17% had no history of AF. MVs were isolated from 150 μL citrate plasma by a four-step differential centrifugation protocol (20000g x 40 min as main pelleting step). The MVs were characterized by immunoblotting and nanoparticle tracking analysis. The size of the MVs ranged between 50 and 600 nm and the MVs were shown to carry typical markers such as Annexin V. For flowcytometric analysis and quantification, Calcein AM was used to identify vesicles and CD31-PE, CD41-APC, CD235a-PE-Cy7 were applied to differentiate between platelet-derived MVs (PMVs, CD41+ CD31+), endothelial cell-derived MVs (EMVs, CD41- CD31+) and Red blood cell-derived MVs (RMVs, CD235a+). Fluorescence minus one controls, a concentration row and detergent mediated degradation were used to confirm specific staining of MVs. Total MV numbers (Calcein + events) did not differ significantly between the three cardiac localizations. In the left atrial appendage, the proportion of PMV was significantly higher in permanent AF patients compared to non-permanent AF. EMV numbers only differed in the right atrium, where permanent AF patients exhibited significantly lower numbers of EMVs compared to no AF controls. No differences between the groups were detected for RMV. Conclusion: In the present study, we found that PMV levels in the left atrial appendage correlate with the type of atrial fibrillation (permanent vs non-permanent). PMVs have been connected to platelet activation and thrombus formation. These results may help to better understand how different types of atrial fibrillation cause different rates of thrombus formation in the LAA. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Medical Faculty University Bonn